Xanthine oxidase activity in thiopurine curative Chinese inflammatory bowel disease patients - Liang Ding; Fang‐bin Zhang; Hui Liu; Xiang Gao; Hui‐chang Bi; Ling Huang; Xue‐ding Wang; Bai‐li Chen; Yu Zhang; Chuanzhu Lv; Pin‐jin Hu; Min Huang (Wiley, 2021)
Abstract Xanthine oxidase (XO) competes with thiopurine S‐methyltransferase (TPMT) and hypoxanthine guanine phosphoribosyltransferase (HPRT) to metabolize azathioprine (AZA)/6‐mercaptopurine (6‐MP) in vivo. A retrospective investigation was performed to detect the activity of XO in thiopurine curative Chinese inflammatory bowel disease (IBD) patients. We also evaluated whether a relationship between XO activity and incidence of thiopurine‐induced adverse effects (AEs) existed. Clinical data and blood samples were collected from 140 IBD patients before receiving AZA/6‐MP therapy, and the erythrocyte XO activity was measured. The XO activities of all patients were 20.29 ± 4.43 U/g Hb. No sex difference in XO activity was observed (p = .728), and the XO activity showed no difference between the UC and CD patients (p = .082). AEs were observed in 41 (29.3%) patients including leukopenia (26, 18.57%), gastrointestinal intolerance (11, 7.86%), flu‐like symptom (5, 3.57%), alopecia (5, 3.57%), and hepatotoxicity (1, 0.71%). XO activity was significantly lower in the patients with AEs than in those without AEs (18.40 ± 3.73 vs. 21.07 ± 4.48 U/g Hb, p = .001), especially in the patients with leukopenia (18.29 ± 3.68 vs. 21.07 ± 4.48 U/g Hb, p = .004). However, no significant difference in XO activity was found between patients with and without other AEs. Decreased XO activity was observed in the patients who developed flu‐like symptoms (17.58 ± 3.50 U/g Hb) and alopecia (18.67 ± 2.91 U/g Hb) compared to those who did not, although the differences did not reach statistical significance. These findings suggested that patients with low XO expression might have a high risk of thiopurine‐induced toxicity.